PERFORMANCE OF WEANER PIGS FED DIETS CONTAINING DIFFERENT PROPORTIONS OF DRIED CASSAVA PEELS AND WHOLE MAIZE. - NWAKPU, P.E.; OMEJE, S.S.I.; ODO, B.I. (Nigerian Journal of Animal Science, 2023)
Twenty - four hybrid (large white x landrace) weaner pigs between 50 - 60 days of age, averaging 8.5 2.5kg were used in a 70 day feeding trials to evaluate the performance of pigs fed dried cassava peels (DCP) and whole maize (wm) in various proportions. Diets 1, 2, 3 and 4 contained 50, 40, 30 and 20% and 0, 10, 20, and 30% wm respectively. Diet 1 was the control, with 50% dried cassava peels. The parameters measured were live weight, feed intake, weight gain, feed conversion ratio (FCR), body length, height at withers and heart girth measurements. Results indicated no significant (P>0.05) differences in the efficiency of feed utilization of the test diets even though, diet 4 had the best feed efficiency. The control diet was superior to other test diets in their feed intake measurements. The body anthropometric measurements followed the same trend as in feed intake except in body weight which excelled in diet 4. In terms of economy and cost benefit, diet 3 was the cheapest followed by diets 1, 2, and 4. Dietary inclusion of DCP and wm at 30 and 20°h respectively resulted in better economics of production. Diet 4, with high content of maize, had the best feed conversion efficiency but failed to induce the most profitable pig growth. Although, diet 3, with 30% DCP*and 20% wm was less efficient in promoting growth, it was more cost effective and increased profitability because 30°/0 DCP and 20% whole maize are cheaper than 50% dried cassava peels as ingredients for weaner pig rations.